Aerobic degradation of 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (DDT) by Alcaligenes eutrophus A5. - Nadeau, L J (1994)
Biotransformation of 1,1,1-trichloro-2,2-bis(4-chlorophenyl)ethane (DDT) by Alcaligenes eutrophus A5 was demonstrated by analysis of ethyl acetate-extracted products from resting cell cultures. Gas chromatography-mass spectrometry characterization of the neutral extracts revealed two hydroxy-DDT intermediates (m/z = 370) with retention times at 19.55 and 19.80 min that shared identical mass spectra. This result suggested that the hydroxylations occurred at the ortho and meta positions on the aromatic ring. UV-visible spectrum spectrophotometric analysis of a yellow metabolite in the culture supernatant showed a maximum A402 with, under acidic and basic conditions, spectrophotometric characteristics similar to those of the aromatic ring meta-cleavage products. 4-Chlorobenzoic acid was detected by thin-layer chromatography radiochemical scanning in samples from mineralization experiments by comparison of Rf values of [14C]DDT intermediates with that of an authentic standard. These results were further confirmed by gas chromatography-mass spectrometry analysis. This study indicates that DDT appears to be oxidized by a dioxygenase in A. eutrophus A5 and that the products of this oxidation are subsequently subjected to ring fission to eventually yield 4-chlorobenzoic acid as a major stable intermediate.